(untitled) (Global Journal of Human-Social Science, 2012)
Women have had a long history in asserting their rights It is a commonly accepted view that the male-dominated patriarchal society and power structure would usually keep the position of women low This powerless situation of women has itself made them to look for a way out and liberation Reformation thinking feminist movements freedom struggle have all contributed in awakening their consciousness Women empowerment refers to strengthening women s position in social economic and political power structure of the society It also implies capacity building with the leading role plagued by the State and non-state organizations